1999
DOI: 10.1017/s0022112098003772
|View full text |Cite
|
Sign up to set email alerts
|

Helical vortices in swirl flow

Abstract: Helical vortices in swirl flow are studied theoretically and experimentally.A theory of helical vortices has been developed. It includes the following results: an analytical solution describing an elementary helical vortex structure – an infinitely thin filament; a solution for axisymmetrical vortices accounting for the helical shape of vortex lines and different laws of vorticity distribution; a formula for calculation of the self-induced velocity of helical vortex rotation (precession) in a cylindri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
125
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(137 citation statements)
references
References 36 publications
10
125
0
2
Order By: Relevance
“…As the local circumferential velocity increases at the cavity centre the pressure decreases and, due to cavitation, forms thin air-filled continuous filaments (see figure 9, top row). From the air bubble visualizations of the helical vortices it is possible to estimate the dimensionless helical pitch τ (Alekseenko et al 1999) which is found to have the same value of approximately τ = 0.8, independent of the type of multiplet. By using the difference between the measured tangential velocity profiles and the analytical expression (2.3), it is possible to determine circulation ratios γ as well as δ, the ratio between the radius of the assigned flow and the radius of the multiplet.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the local circumferential velocity increases at the cavity centre the pressure decreases and, due to cavitation, forms thin air-filled continuous filaments (see figure 9, top row). From the air bubble visualizations of the helical vortices it is possible to estimate the dimensionless helical pitch τ (Alekseenko et al 1999) which is found to have the same value of approximately τ = 0.8, independent of the type of multiplet. By using the difference between the measured tangential velocity profiles and the analytical expression (2.3), it is possible to determine circulation ratios γ as well as δ, the ratio between the radius of the assigned flow and the radius of the multiplet.…”
Section: Resultsmentioning
confidence: 99%
“…Note that the same vortex model (2.3), in the sense of Batchelor's vortex (Batchelor 1964) or the q-vortex, is commonly used to describe experimental swirl flows (Faler & Leibovich 1978;Escudier 1988;Alekseenko et al 1999) and in instability studies of swirling flows (see Heaton & Peake 2007 and references therein).…”
Section: Multiple Helical Modes Of Vortex Breakdownmentioning
confidence: 99%
“…an influence of the downstream conditions on the entire flow), and vortex breakdown. Theoretical work on swirling flow [4,5] is often based on the Euler equations, leaving out turbulence. Industrial flows are, however, in many cases turbulent due to the large scale of the equipment, and high throughput.…”
Section: Introductionmentioning
confidence: 99%
“…To carry out the experiments, a hydrodynamic stand created earlier in the IT SB RAS [2] to study turbulent swirling flow has been modernized. The hydrodynamic stand (Fig.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Longitudinal concentrated vortices increase the efficiency of devices and hardware systems. Stationary helical vortex structures were first observed at the Institute of Thermophysics of the SB RAS [2]. Until now, there is no quantitative information on such vortices that hinders understanding the physics of formation of vortices and developing approaches for mathematical description of the vortex dynamics.…”
Section: Introductionmentioning
confidence: 99%